The Baclaran Gateway revitalizing Baclaran as a commercial and transit-oriented district - Go, Samantha Andrea Monique H.; Santos, Frederick C. (Quezon City College of Architecture, University of the Philippines Diliman, 2020)
Baclaran is visited by many for the well-known Redemptorist Church and its high level of commercial activity. Over time, the district has grown to become one of the most visited commercial areas in the metro. However, there has been a decline in the vitality and vibrancy of Baclaran as a commercial district, due to the clearing of street vendors. The usual lively streets of Baclaran, filled with so many people who go shopping or visit the church, are not so lively anymore. Additionally, the influx of vehicles has made the flow of pedestrians travelling from one point to another uneasy and obstructive. This project aims to explore how we can integrated the informal vendors into a more formal environment, while developing a more efficient pedestrian flow, thus retaining the vibrancy of the district. The Baclaran Gateway is a redevelopment of the district's tiangge malls and streets to create efficiency in the flow of movement of its users, while formalizing the informal vendor community. This project shows how site-specific, user behavior-based design and extensive research can develop a project that addresses current problems and adapts to future changes.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Flea markets -- Baclaran (Manila)